2022
DOI: 10.3159/torrey-d-22-00008.1
|View full text |Cite
|
Sign up to set email alerts
|

Leaf phenology and freeze tolerance of the invasive tree Pyrus calleryana (Roseaceae) and potential native competitors1

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Based on this sprout response, there is no evidence to support freezing as a control treatment for P. calleryana. Maloney et al (2022) recently reported an extended phenology in P. calleryana including early leaf on, late leaf off, and tolerance to a frost event that suggested that this species may be biologically more tolerant of cold conditions than native species. While our experiment yielded no evidence of freeze vulnerability in this species, the use of freezing as an experimental control mechanism may be useful for other invasive species, particularly those with a home range characterized by mild winters.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this sprout response, there is no evidence to support freezing as a control treatment for P. calleryana. Maloney et al (2022) recently reported an extended phenology in P. calleryana including early leaf on, late leaf off, and tolerance to a frost event that suggested that this species may be biologically more tolerant of cold conditions than native species. While our experiment yielded no evidence of freeze vulnerability in this species, the use of freezing as an experimental control mechanism may be useful for other invasive species, particularly those with a home range characterized by mild winters.…”
Section: Discussionmentioning
confidence: 99%
“…(Shi et al 2006) and Norway maple (Acer platanoides L.) (Morrison and Mauck 2007), P. calleryana can adapt to its environment such that advanced-generation hybrids exhibit higher photosynthetic and transpiration rates than early-generation hybrids (Merritt et al 2014). Once established in an environment, the tree's long-lived seeds, occasional thorny phenotype, fire resistance, and capacity to resprout after topkilling make controlling established populations cost-and laborintensive (Coyle et al 2021;Culley and Hardiman 2007;Hay 2021;Serota and Culley 2019;Warrix and Marshall 2018). Further, as genetic admixture between populations continues into advanced generations, the "cultivation-adapted" trees may lose detrimental traits associated with artificial selection and become more invasive (Hardiman and Culley 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrus calleryana also exhibits many traits associated with both stress tolerance and fast growth. The tree exhibits relatively long leaf phenology compared with native species and is resistant to short-term frost events, potentially allowing it to outcompete native species via its extended growing season (Maloney et al 2022). Additionally, while the photosynthetic characteristics of P. calleryana are comparable to those of other woody deciduous species and measurements conducted by Merritt et al (2014) indicate that it has a lower mean photosynthetic rate than those reported for woody invaders butterfly bush ( Buddleja davidii Franch.)…”
Section: Introductionmentioning
confidence: 99%